Casson hybrid nanofluid natural convection in trapezoidal cavity containing a partially heated wall - Md Arifin, Norihan; Saleh, Habibis; Hashim, Ishak; Azizul, Fatin Munirah (Semarak Ilmu Publishing, 2022)
A computational analysis has been performed for Casson hybrid nanofluid natural convection heat transfer in trapezoidal cavity containing a partially heated at bottom wall, and the incline walls are set to be at the cold temperature while the top wall is supposed to be adiabatic. The hybrid nanoparticles, alumina and copper are dispersed in ethylene glycol and water mixture has been used as a working fluid. The finite element method is used to solve the nondimensional governing partial differentials equations. The numerical results are carried out for different governing parameters such as Casson parameter Rayleigh number and hybrid nanoparticles volume fraction and heated zone length. The influence of these parameters on streamlines, isotherms, velocities and average Nusselt number will be the focus in this study.